Raisin, vin, vinaigre, verjus dans les traités culinaires… ou « Dans la vigne tout est bon » - Perrine Mane (L'Atelier du CRH)
Besides the consumption of wine as drink, the grape is greatly used in medieval cooking. So are its other liquid by-products, such as vinegar, verjuice or must. The cookbooks which spread all over the West from the 13th century onwards, but mainly in the 14th and 15th centuries, are a testimony to these important uses.